PENGOLAHAN KUDAPAN SEHAT SEBAGAI UPAYA MENGATASI STUNTING BAGI ANAK-ANAK DI DESA HILI AMAODULA KECAMATAN PULAU-PULAU BATU - Zalukhu, Merri Christina (Universitas Nias Raya, 2024)
The problem of stunting is one of the important issues in the world of children's health that is still a major concern. Hili Amaodula Village, one of the villages located in the administrative area of ​​Pulau-Pulau Batu sub-district, South Nias, experiences stunting problems with several characteristics such as children's height and weight being smaller than children of the same age, experiencing growth and development disorders, looking weak all the time, being prone to health problems, and being less active. Therefore, it is considered good to empower PKK (Family Welfare Supervisors) mothers to process foods such as snacks with natural ingredients containing carbohydrates, iron, protein, vitamins, calcium, and iron that support children's health development. These healthy snacks are processed with various variants that are liked by mothers and children and can support the health of the residents of Hili Amaodula Village. The objectives of this program are 1) as an effort to improve the healthy lifestyle of the people of Hili Amaodula Village, Pulau-Pulau Batu Sub-district; 2) an effort to reduce and prevent stunting in Hili Amaodula Village; 3) efforts to build the creative potential of mothers in managing healthy snacks for families; 4) as a place for mothers to learn to sort clean and healthy food ingredients. The implementation method is carried out in three stages: preparation, implementation (socialization, training, exhibition/bazaar), and evaluation and reporting. Based on the results of interviews and observations, the people of Hili Amaodula village were very enthusiastic about participating in this activity, especially the PKK mothers. The knowledge and initiative of the PKK mothers also increased. The Village Government hopes that community activities like this can be sustainable.